2017
DOI: 10.18805/ijare.a-4106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated seed treatments on growth, seed yield and quality parameters in black gram [Vigna mungo (L.) Hepper]

Abstract: Pulses are one of the most important legume crops in India contributing significantly high quality protein. Among the legumes, black gram (Vigna mungo L. Hepper), is an important legume crop in our country belonging to the family leguminoceae. The low productivity in pulses may be due to the fact that they are normally grown in marginal lands with inadequate soil moisture and poor fertility status. To increase yield under these circumstances, integrated seed treatment is given as a presowing treatment. Hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Among the treatments, Polymercoat @ 3 ml/kg + Saaf @ 3 g/kg + P. fluorescens @ 30 g/kg of seeds recorded significantly highest number of pods per plant and seeds per pod (18.80 and 12.60) over untreated control (11.60 and 8.53).The increase in number of pods may be due to the more number of branches per plant, decreased flower drop, increased pod setting, nutrient mobilization, nutrient uptake, release of plant growth promoting substances by microbial inoculants and antagonistic activity against pathogens. Similar response due to seed treatment was observed by Tripathi and Singh (1991), Kanti et al, (2013) and Narayanan et al, (2017) in blackgram.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Among the treatments, Polymercoat @ 3 ml/kg + Saaf @ 3 g/kg + P. fluorescens @ 30 g/kg of seeds recorded significantly highest number of pods per plant and seeds per pod (18.80 and 12.60) over untreated control (11.60 and 8.53).The increase in number of pods may be due to the more number of branches per plant, decreased flower drop, increased pod setting, nutrient mobilization, nutrient uptake, release of plant growth promoting substances by microbial inoculants and antagonistic activity against pathogens. Similar response due to seed treatment was observed by Tripathi and Singh (1991), Kanti et al, (2013) and Narayanan et al, (2017) in blackgram.…”
Section: Resultssupporting
confidence: 86%
“…The increased yield was attributed to better plant establishment with suppression of seed borne diseases. Similar studies were conducted by Narayanan et al, (2017) in black gram who reported that seeds fortified with MgSO 4 + polykote + carbendazim + dimethoate + bioinoculant (P. fluorescens) + Rhizobium + Azophos + pelleting with DAP recorded higher seed yield and other parameters when compared to control. Similar findings were also observed by Rajeswari and Meena (2009) in soybean.…”
Section: Resultssupporting
confidence: 81%
“…At present, pre-sowing seed treatment one of the most effective ways to increase the productivity of agricultural crops by plant growth regulators with microelements are considered as an environmentally friendly and economically profitable way to increase the yield of cereals through accelerating germination and improving seedling growth (Narayanan et al, 2017). That is one of the trends in sustainable agriculture that increases plant resistance to the effects of unfavorable environmental factors.…”
Section: Introductionmentioning
confidence: 99%